Posters for Peace : Visual Rhetoric and Civic Action - Benson, Thomas W. (Book collections on Project MUSE., 2015)
"A rhetorical history of Vietnam War era posters produced at the University of California, Berkeley, in the spring of 1970. Places the posters in the contexts of the politics of the 1960s and the history of political graphics"--Provided by publisher